Control Banding for wastes: a spreadsheet for a simple and fast comparison of impact on the enviroment of wastes with chemical substances - Rodríguez Corrales, José Ángel (2013)
Diminishing the polluting effect of wastes upon citizens and the environment represents an important aim to fulfill to guarantee a better life quality and a sustainable development. To address this problem a classification system of any chemical output and a score based in the quantity and danger was obtained by a control banding technique. By developing a spreadsheet based in this concept, the entries were specified for the chemical and toxic properties of any substance with a MSDS registry. From this work, it was obtained a classification based in the quantity, concentration, known toxicity and effects (i.e. LD50 and Risk Phases, known as R phrases) inside a fixed scale for each point. This tool can be applied to several situations where chemical wastes cannot be assessed once they are eliminated.